A PI Queueing Delay Controller Enhanced by Adaptive CHOKe for AQM - Siqiao Hu; Jinsheng Sun; Zhengfei Liu; Qin Xu (IEEE Access, 2018)
In typical access networks, the bandwidth available to individual users is ever-changing, which aggravates the effects of bufferbloat. Instead of queue length, adopting queuing delay as the control objective for Active Queue Management (AQM) algorithms helps guarantee a uniform performance should congestion appear. This paper proposes a fairness-oriented AQM named D-PAC based on an adaptive CHOKe mechanism and the proportional-integral (PI) queuing delay controller. It is designed to protect responsive traffic from unresponsive flows while keeping the queuing delay satisfactory. D-PAC improves fairness by actively adjusting the number of CHOKe comparisons according to the ratio of successful comparisons. Properties of the proposed adaptive CHOKe mechanism are analyzed. Simulation results confirm that D-PAC is able to improve the inter-flow fairness by various criteria, protect short flows from unresponsive traffic, and keep the queuing delay short and stable.